Alcaligenes ammonioxydans HO-1 antagonizes Bacillus velezensis via hydroxylamine-triggered population response - Gao, Xi-Yan; Xie, Wei; Liu, Ying; Ma, Lan; Liu, Zhi-Pei (Frontiers in Microbiology, 2022)
Antagonism is a common behavior seen between microbes in nature. Alcaligenes ammonioxydans HO-1 converts ammonia to nitrogen under aerobic conditions. This leads to the accumulation of extracellular hydroxylamine (HA), providing pronounced growth advantages against many bacterial genera, including Bacillus velezensis V4. In contrast, a mutant variant of A. ammonioxydans, strain 2-29 that cannot produce HA, fails to antagonize other bacteria. Here we demonstrate that cell-free supernatants derived from the antagonistic HO-1 strain was sufficient to reproduce the antagonistic behavior and the efficiency of this inhibition correlated strongly of with the HA content of the supernatant. Furthermore, reintroducing the capacity to produce HA to the 2-29 strain, or supplementing bacterial co-cultures with HA restored antagonistic behavior. The HA-mediated antagonism was dose-dependent and was affected by the temperature but not by pH. HA caused a decline of biomass, cell aggregation, and hydrolysis of the cell wall in exponentially growing B. velezensis bulk cultures. Analysis of differential gene expression identified a series of genes modulating multicellular behavior in Bacillus velezensis. Genes involved in motility, chemotaxis, sporulation, polypeptide synthesis, and non-ribosomal peptide synthesis were all significantly down-regulated in the presence of HA, while autolysis-related genes showed up-regulation. Taken together, these findings indicate that HA affects the population response of co-existing strains. These findings suggest that A. ammonioxydans HO-1 antagonize other bacteria by producing extracellular HA that, in turn, and acts as a signaling molecule.